A rágalmazás „tényállása” az Ószövetségben és a rabbinikus jogtudományban - Ruff, Tibor (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2024)
The Law of Moses, the Torah, does not explicitly divide the crimes that can be committed in the field of communication into criminal and civil categories, contrary to the legal system of modern and postmodern European states. In the theocratic legal system of the ancient state of Israel, where all sins against human beings were first and foremost offences against God (i.e., being a holy nation, they were also a matter of holiness), this distinction was at most separable in the way in which cases were dealt with, and in the fact that prosecution of certain crimes was mandatory, while prosecution of others was, in modern terms, on the basis of private accusation. The Ten Commandments forbid two acts of communication: the vain (empty, meaningless, false, blasphemous, etc.) use of the name of God (Yhwh), and, in human relations, bearing false witness against someone. In my study, I intend to give an overview of the latter element of the Ten Commandments as a general clause, using the Torah and the sources of rabbinic jurisprudence and relevant literature in a historical context.